(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of stress and stress coping strategies among nurses at Le Van Thinh Hospital in 2024. Subjects and Methods: This is a cross-sectional descriptive study. A survey was conducted with 205 nurses who had been working for more than 12 months and agreed to participate. The screening tool used was the DASS-21 (Depression-Anxiety-Stress Scale-21), and coping strategies were assessed using the CBI (Coping Behavior Inventory), a tool measuring occupational burnout. The study utilized a self-administered questionnaire. Results: The findings revealed that 25.5% of nurses showed signs of stress, including mild stress (9.3%), moderate (9.3%), severe (6.3%), and very severe (0.5%). The most commonly used coping strategy was stress relief methods, followed by optimistic approaches to stress, direct problem-solving, and lastly, avoidance behaviors. Conclusion: The results indicate that over 25% of the nurses in the study experienced stress, highlighting the importance of supporting nurses in managing and relieving stress.